2015
DOI: 10.11646/zootaxa.3919.2.3
|View full text |Cite
|
Sign up to set email alerts
|

An annotated checklist of the Recent non-marine ostracods (Ostracoda: Crustacea) from Italy

Abstract: We present an updated checklist of non-marine ostracods from Italy. Data were obtained from the published literature up to April 2013 and new collections carried out in 18 out of 20 Italian regions. Altogether, 1665 ostracod samples were collected from 1241 new sites visited between 1981 and 2013. Sites were selected to encompass the most widespread types of freshwater aquatic habitats (i.e., pools, ponds, peat bogs, springs and streams, etc.). This field study led to the identification of 89 ostracod species.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…Pseudocandona and Candona are freshwater-mesohaline taxa found only within the uppermost samples, frequent in European ponds and lakes (Meisch, 2000;Pieri et al, 2005).…”
Section: Inner Lagoon Assemblage (Assemblage 1)mentioning
confidence: 99%
“…Pseudocandona and Candona are freshwater-mesohaline taxa found only within the uppermost samples, frequent in European ponds and lakes (Meisch, 2000;Pieri et al, 2005).…”
Section: Inner Lagoon Assemblage (Assemblage 1)mentioning
confidence: 99%
“…and Degrassi, 1995), Bracciano (Mastrantuono, 1995), and Martignano (Mastrantuono and Mancinelli, 2003). Additionally, Pieri et al (2015) reported ostracods from some small mountain lakes in Piedmont, the Dolomites (northern Italy) and the central Apennines (Abruzzo Region). However, only few of these studies analyse the presence of ostracods in their environment, linking their assemblages with the dominant physical, chemical and biological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The 19 species collected among the living meiobenthos of Lake Trasimeno are widely recorded in other Italian freshwater or brackish sites (Pieri et al, 2015) but three of them (C. torosa, I. salebrosa, L. stationis) deserve an in-depth discussion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations